A 0.044-mm2 0.5-to-7-GHz resistor-plus-source-follower-feedback noise-cancelling LNA achieving a flat NF of 3.3±0.45 dB - Yu, Haohong (2019)
A wideband noise-cancelling low-noise amplifier (LNA) combining resistor feedback and source-follower feedback (SFF) is proposed. The SFF facilitates upsizing of the feedback resistor to improve the gain and noise figure (NF), without compromising the input-impedance matching. Another benefit is that the noise contributions of both the feedback resistor and noise-cancelling transistors are significantly reduced. Fabricated in 65-nm CMOS, the LNA exhibits a voltage gain of 16.8 dB, and a flat NF of 3.3 ± 0.45 dB over a −3-dB bandwidth of 0.5 to 7 GHz. The power consumption is 11.3 mW at 1.2 V, and the die area is 0.044 mm2